Podstawowe zmiany w poziomie i strukturze konsumpcji w Polsce Ludowej - Piasny, Janusz (Wydział Prawa i Administracji UAM, 1970)
The tendencies discussed in the paper pertain to the consumption resulting from personal incomes during the 25-years' period in the Polish People's Republic. A constant growth of incomes of the population has been found to be accompanied by an increase of the general level of consumption per capita and essential changes have been observed in the structure of consumption this being true as for town as for countryside. The systematic decrease in the consumption of goods of the lower order has been stated to be followed by a constant increase in purchases of the goods that meet the demands of the higher order. This increase has appeared so significant that in spite of the quantitative as well as of the qualitative development on the diet pattern the contribution of means spent on food to the total expenditure has been stated to decrease systematically. A continued increase in consumption and rapid changes of its structure in farmers' families have resulted in a marked tendency to diminishing differences between the town and countryside consumption patterns. Contrary to the pre-war period during which these differences were very deep almost full equlization has been obtained as far as the food consumption is concerned, a fairly good resemblance being achieved in the purchase pattern of clothes, footwear, underclothing and the differences have been considerably reduced concerning expenses on personal hygiene, health protection, culture and education. A decrease in differences has been also observed as far as the household equipment is concerned, such as furniture, televisors, radio sets, washing machines, sewing machines, vacuum cleaners and other house utensils as well. As regards the consumption of foods the following tendencies have been observed: democratization of consumption as shown by the decrease in differences of the diet pattern between different social and professional groups of the population, an increasing contributions of the richer in vitamins and animal proteins, foods of higher quality to the diet pattern, the high rate of increase in the food consumption combined with its constant denaturalization especially in the country. As far as the level of consumption is concerned Poland has approached that of the highly developed countries. The differences that are still being observed especially those concerning the consumption of fish, cheeses, fruits and some vegetables have no structural character and can be eliminated in a relatively short time.
Basic Changes in Level and Structure of Consumption in the Polish People's Republic